Storytelling Activities of the Story of Prophet Ayub AS at RA Dewi Masyithoh for the Formation of Children's Religious Characters in the Golden Age Phase - Zaenol Fajri; Atik Hikmatuz Zakiyah (Universitas Muhammadiyah Makassar, 2022)
Early childhood is the